2003
DOI: 10.1007/s00421-003-0792-8
|View full text |Cite
|
Sign up to set email alerts
|

Functional and biochemical properties of chronically stimulated human skeletal muscle

Abstract: The present study was undertaken to investigate in a randomized controlled trial the effects of chronic (10 weeks, 4 h per day, 7 days per week) low-frequency (15 Hz) stimulation (CLFS) of the knee extensor and hamstring muscles of both legs in healthy volunteers via surface electrodes. A control group (n=10) underwent the same treatment (sham stimulation) as the CLFS-treated group (n=10), except that stimulation intensity was kept at a level which did not evoke contractions. Biopsy samples were taken before t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
72
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(81 citation statements)
references
References 43 publications
8
72
0
1
Order By: Relevance
“…Consistent with the results obtained in healthy males [31], paraplegic males [32] and chronic heart failure patients [33] after an electrostimulation programme, we observed an increase in type I fibre proportion and a decrease in type IIx fibre proportion in COPD patients after exacerbation. These changes are usually interpreted as transition from fast-to-slow fibre type.…”
Section: Muscle Structuresupporting
confidence: 91%
“…Consistent with the results obtained in healthy males [31], paraplegic males [32] and chronic heart failure patients [33] after an electrostimulation programme, we observed an increase in type I fibre proportion and a decrease in type IIx fibre proportion in COPD patients after exacerbation. These changes are usually interpreted as transition from fast-to-slow fibre type.…”
Section: Muscle Structuresupporting
confidence: 91%
“…Within the framework of PR, transcutaneous neuromuscular electrical stimulation (NMES) of the lower limb muscles increases muscular oxidative capacities [28]. Small controlled studies with this technique in severe and even bed-bound COPD patients have been reported [29][30][31][32][33][34][35].…”
Section: Transcutaneous Neuromuscular Electrical Stimulationmentioning
confidence: 99%
“…Kim et al (21) reported, after a NMES training program, no changes in citrate synthase activity and number of capillaries. Nuhr et al (35) showed an increase in the activity of citrate synthase associated with a decrease in the activity of glyceraldehyde phosphate dehydrogenase. Interestingly, these molecular adaptations were not associated with clear effects in vivo.…”
mentioning
confidence: 98%
“…Perez et al (36) observed an increase of the mean number of capillaries of fast-twitch (type II) fibers, but only minimal muscle hypertrophy, and no significant changes in aerobic performance. On the other hand, Nuhr et al (35) reported an improved work capacity and O 2 uptake (V O 2 ) at the anaerobic threshold following NMES. Compared with voluntary contractions of the same intensity, it has been reported that contractions obtained by NMES are associated with a greater (30,32) or similar (33) metabolic demand, and with an increased blood flow during recovery (32,45).…”
mentioning
confidence: 99%